(untitled) (World Economics and Finance Bulletin, 2022)
As a result of consistent reforms in the agricultural sector in this article, the introduction of a new system of agricultural production - the introduction of a new system of agricultural sector is reported that the introduction of cluster methods is opened in agriculture, particularly the opening of large potential in the field of cotton textiles